Well‐Defined Single‐Site Monohydride Silica‐Supported Zirconium from Azazirconacyclopropane. Issue 11 (13th January 2015) - Hamzaoui, Bilel; Eter, Mohamad El; Abou‐hamad, Edy; Chen, Yin; Pelletier, Jérémie D. A.; Basset, Jean‐Marie
Abstract The silica‐supported azazirconacyclopropane SiOZr(HNMe2)(η2‐NMeCH2)(NMe2) (1) leads exclusively under hydrogenolysis conditions (H2, 150 °C) to the single‐site monopodal monohydride silica‐supported zirconium species SiOZr(HNMe2)(NMe2)2H (2). Reactivity studies by contacting compound 2 with ethylene, hydrogen/ethylene, propene, or hydrogen/propene, at a temperature of 200 °C revealed alkene hydrogenation.